Physicomechanical properties of nanobiocomposite composed of polylactic acid and biogenic nano hydroxyapatite - Bano, N.; Jikan, S.S.; Basri, H.; Adzila, S.; Badarulzaman, N.A. (Penerbit UTHM, 2019)
In the current paper, nanobiocomposite consisting of polylactic acid (biodegradable) (PLA) and nanohydroxyapatite (bioactive) (n-HAP) extracted from bovine bone was fabricated through melt mixing and injection moulding technique for biomedical applications. Partially biogenic nanohydroxyapatite was obtained from bovine bone by hydrothermal method and calcination treatment without using of any chemicals/solvents. Physicomechanical properties of neat-PLA and PLA/n-HAP nanobiocomposite were evaluated using X-ray diffraction (XRD), universal testing machine (UTM) and scanning electron microscopy (SEM). XRD result showed that the intensity of n-HAP peaks increased in the nanobiocomposite as n-HAP-900 loading increased. Tensile strength decreased with increasing the n-HAP-900 loading from 56.78 to 48.25 MPa due to poor interfacial adhesion between neat-PLA and n-HAP. PLA/n-HAP with 1% loading exhibits tensile strength potential for bone implant application and can be promising biomedical materials for orthopedic applications.